Molecular cloning, characterization, and expression profiles of the Sox3 gene in Chinese loach Paramisgurnus dabryanus. Issue 3 (23rd March 2018) - Xia, Xiaohua; Huo, Weiran; Wan, Ruyan; Wang, Peijin; Zhang, Linxia; Chang, Zhongjie
Abstract : A number of studies have established that in vertebrates, Sox3 is involved in a wide range of developmental processes, including sex differentiation and neurogenesis. However, the exact functions of the Sox3 gene have not been documented so far in teleosts. Here, we cloned the full length cDNA of Sox3 from the teleost fish, Paramisgurnus dabryanus, which we designated PdSox3 . Sequence analysis revealed that PdSox3 encodes a hydrophilic protein, and shares high homology with Sox3 in other species, ranging from mammals to fishes. Quantitative real‐time reverse transcription PCR, and in situ hybridization showed that PdSox3 is consistently expressed during embryogenesis, mainly localized in the developing central nervous system. Tissue distribution analyses revealed that PdSox3 is abundant in the adult brain, especially in particle cell layer. Furthermore, PdSox3 expression was higher in gonads, in primary spermatocyte cells, primary oocytes, and previtellogenic oocyte cells. All of these results suggest that PdSox3 plays an important role in early embryonic development, in particular the formation and development of the nervous system, and gonad development, similarly to other vertebrates. This is the first report describing Sox3 gene expression from this species, and the results are necessary to provide fundamental information on both the functional and evolutionary role of Sox3 across different species.